1,4-Dihydropyridine as a Promising Scaffold for Novel Antimicrobials Against Helicobacter pylori - González, Andrés; Casado, Javier; Gündüz, Miyase Gözde; Santos, Brisa; Velázquez-Campoy, Adrián; Sarasa-Buisan, Cristina; Fillat, María F.; Montes, Milagrosa; Piazuelo, Elena; Lanas, Ángel (Frontiers in Microbiology, 2022)
The increasing occurrence of multidrug-resistant strains of the gastric carcinogenic bacterium Helicobacter pylori threatens the efficacy of current eradication therapies. In a previous work, we found that several 1,4-dihydropyridine (DHP)-based antihypertensive drugs exhibited strong bactericidal activities against H. pylori by targeting the essential response regulator HsrA. To further evaluate the potential of 1,4-DHP as a scaffold for novel antimicrobials against H. pylori, we determined the antibacterial effects of twelve novel DHP derivatives that have previously failed to effectively block L- and T-type calcium channels. Six of these molecules exhibited potent antimicrobial activities (MIC ≤ 8 mg/L) against three different antibiotic-resistant strains of H. pylori, while at least one compound resulted as effective as metronidazole. Such antimicrobial actions appeared to be specific against Epsilonproteobacteria, since no deleterious effects were appreciated on Escherichia coli and Staphylococcus epidermidis. The new bactericidal DHP derivatives targeted the H. pylori regulator HsrA and inhibited its DNA binding activity according to both in vitro and in vivo analyses. Molecular docking predicted a potential druggable binding pocket in HsrA, which could open the door to structure-based design of novel anti-H. pylori drugs.